Psychological Expert Witness Work in Indonesia - Arbiyah, Nurul; Sumampouw, Nathanael; Otgaar, Henry (UI Scholars Hub, 2026)
In the current manuscript, we describe how forensic psychology evolved in Indonesia in research and practice settings and how psychologists work as expert witnesses in legal cases. We performed a literature search using SINTA (the portal of Indonesian accredited journals) to retrieve publications on